Individual Accountability in International Economic Policymaking after the Global Financial Crisis - Stefano Pagliari; Iosif Kovras (City, University of London, City Political Economy Research Centre (CITYPERC), 2021)
In the aftermath of the global financial crisis, the design of accountability mechanisms has taken on renewed importance in academic and policy debates. Calls for holding individuals whose actions and omissions contributed to the meltdown accountable have gained traction in a number of countries after the crisis. Yet, individual accountability norms are seemingly absent from the international economic agenda in response to crisis. In this paper we address this puzzle by exploring the evolution of two major international organisations, the IMF and the FSB, in bringing accountability following financial crises. Our analysis reveals how these institutions have increasingly incorporated in their toolkit policy recommendations related to the unethical or illegal conduct by government officials of individuals in the financial industry, but these tools were geared almost exclusively towards forward-looking policies designed to deter the reoccurrence of illegal or unethical behavior rather than punishing or scrutinizing past wrongdoing. We argue that the extent to which individual accountability norms permeate the international economic agenda is mediated by the institutional characteristics of the organizations that comprise the international financial regime.
Keywords: 330; Accountability; Financial Crisis; Global Governance; Bureaucratic Culture